KOMBINASI IAA DAN BAP PADA KULTUR BIJI ANGGUR (Vitis vinifera) DALAM MEDIA MURASHIGE & SKOOG (MS) - Panggabean, Nurul Huda; Pratama, Rizky Yuda; Ansyar, Alfan; Selviana, Erika; Marpaung, Dwi Ratna Anjaning Kusuma (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2024)
Economic potential and growing public interest in the grapes have led to the plant having high prospects for cultivation and development in other parts of Indonesia. The aim of this research is to produce quality seedlings through network culture techniques. The method of providing grape seed is relatively fast with the amount of seed produced quite a lot that is through the technique of network culture. The research was conducted from March to May 2023 at the Laboratory of Physiology and Culture of Plant Networks, Faculty of Mathematics and Natural Sciences, University of North Sumatra, Field, North Sumatera. Parameters observed in Vitis vinifera plant tissue culture practices with a combination of IAA and BAP treatment on MS media are growth time, growth percentage and contamination percentages. Data from the study was analyzed using Analysis Of Variance (ANNOVA). If the treatment gives a significant different effect then proceed with the Duncan New Multiple Range Test (DNMRT) at the level of 5% (P 0.05) on the treatment factor.Treatment I1 has the fastest increasing power output with an average growth time of 9 a. Further testing results show that the treatment of IAA and BAP hormones in different media is significantly higher than the control. The results of the study showed that the highest percentage of explanation growth (100%), although it took a relatively longer time to form the calus and shoots.